A strasbourgi bíróság jogfejlesztő tevékenysége és az „európai konszenzus” - Kémeri, Zsófia Eszter (Debreceni Jogi Műhely, 2016)
The European Convention on Human Rightsin collaboration with the European Court of Human Rights created a jurisprudence which is simply the most effective system in international human rightsprotection. Based on the Convention’s Preamble, European countries intend to create a common European legal system and develop the cooperation between the “likeminded European countries” through the common heritage of democracy and the rule of law. Keep pace with the needs of present-day society would be difficult for the Court, but using the principles of interpretation of the Convention, the court seems to be able to maintain a balance between development and stability.With the use of evolutive interpretation, the Convention is a so-called living instrument which means that the Court interpret the document according to the present-day conditions. Based on this assumption, I wish to examine the principle of evolutive interpretation adopted by the Strasbourg Court, which has a major role in the so-called European consensus. In the first part of the essay, I discuss the types of consensus-analyzes using by the Strasbourg court, and later I scrutinize the historical aspects of the evolutive interpretation and its practical relevance in the Court’s case-law. After that, I analyze the justification of the principle and I mention the criticisms formulated against the evolutive interpretation. Finally, I consider that the purposes about the closer union among the European countries established by the Preamble and the effective protection of human rights could not occur without the implementation of evolutive interpretation